2013
DOI: 10.2217/dmt.13.37
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid diabetes and depression: do E-health treatments achieve better diabetes control?

Abstract: SUMMARYResearch in the field of comorbid depression in diabetes shows that the optimum treatment to attain better diabetes disease control is still undecided. Although several treatment models are effective and available, interventions aimed at improving disease control, such as glycemic control, are less effective, with moderate evidence for pharmacological treatment and a lot of evidence for psychotherapy in combination with self-management techniques. New developments such as M-health and E-health are much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…A total of eight randomized controlled trials have evaluated the efficacy of psychotherapeutic interventions on depression in mixed populations of adults with type 1 and type 2 diabetes. Similar beneficial effects of low to moderate effect size have been observed across the studies, indicating the value of this approach in the context of multiple variations in length and format of delivery (e.g., eHealth, individual face-to-face psychotherapy, group psychotherapy) and audience ( 55 ). Further research is needed to improve the efficacy of CBT and determine the minimum meaningful “dose” needed to have the greatest cost-benefit for people with diabetes and health providers.…”
Section: Treatment Of Diabetes and Depressionsupporting
confidence: 62%
See 2 more Smart Citations
“…A total of eight randomized controlled trials have evaluated the efficacy of psychotherapeutic interventions on depression in mixed populations of adults with type 1 and type 2 diabetes. Similar beneficial effects of low to moderate effect size have been observed across the studies, indicating the value of this approach in the context of multiple variations in length and format of delivery (e.g., eHealth, individual face-to-face psychotherapy, group psychotherapy) and audience ( 55 ). Further research is needed to improve the efficacy of CBT and determine the minimum meaningful “dose” needed to have the greatest cost-benefit for people with diabetes and health providers.…”
Section: Treatment Of Diabetes and Depressionsupporting
confidence: 62%
“…For example, trials of eHealth and mobile technology–based health (mHealth) interventions suggest that these are less effective than face-to-face psychotherapeutic treatments (55). …”
Section: Treatment Of Diabetes and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result indicated that depressive symptoms were not significantly lower in the intervention group when compared with control group. However, evidence indicated that psychological therapies like Motivational Interviewing (MI) may also be effective in treating depression in people with diabetes but may have limited effects on glycemic outcomes [ 47 , 48 ]. Two possible reasons for these findings may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The trials have a preponderance of people with type 2 diabetes and no trials have been conducted to date with only people with type 1 diabetes. There is preliminary evidence to suggest the web-based psychological therapies may also be effective in treating depression in people with diabetes but may have limited effects on glycemic outcomes [76, 77]. …”
Section: Treatment Of Diabetes and Depressionmentioning
confidence: 99%